A compact 2-DOF piezo-driven positioning stage designed by using the parasitic motion of flexure hinge mechanism. (2nd December 2019) - Li, Xuan; Wang, Xiangyuan; Sun, Wuxiang; Wang, Kuifeng; Yang, Zhixin; Liang, Tianwei; Huang, Hu
Abstract: This paper presents a compact two-degrees of freedom piezo-driven positioning stage. To achieve large working stroke, the stick-slip principle was employed, and to make the stage compact, a lever-type flexure hinge mechanism (LFHM) with the L-shape structure was designed. The LFHM could tune the single-direction output displacement of the stacked piezoelectric (SPE) to be two directional motions, the main motion for stick-slip driving and the parasitic motion for the contact. The L-shape structure makes the SPE being parallel to the slider rather than vertical to it, and therefore, the stage could be compact. The positioning stage had a two-layer structure for realizing motions along x and y axes, and these two layers shared the same structure. The structure design and working principle of the stage were discussed in detail. A prototype was fabricated, and the effects of driving frequency and voltage on the output characteristics were evaluated, followed by measuring its loading capacity and frequency characteristic. Experimental results showed that the output displacement had very good linearity in both x and y axes and as well for both positive and negative motions. Especially, even for a relatively large displacement output being over 1600 μ m achieved by stepping accumulation, the output displacement still maintained very good linearity, demonstrating good motion stability. Furthermore, the backward motion was quite small compared with some previous studies. In addition, the vertical load in the range of 0–2 N had quite weak effects on the output characteristics, and the first resonant frequency of the driving unit was over 1900 Hz. These results indicated that the designed x – y positioning stage not only had a compact structure but also possessed good performances, which were beneficial to its practical applications.